1998
DOI: 10.1016/s0022-5223(98)70278-8
|View full text |Cite
|
Sign up to set email alerts
|

The Role Of Endothelial Nitric Oxide Synthase Expression In The Development Of Pulmonary Hypertension In Chronically Hypoxic Infant Swine

Abstract: Raising infant piglets in an environment of 10% oxygen for 4 weeks results in significant pulmonary arterial hypertension accompanied by increased expression of nitric oxide synthase within the lung endothelium. Furthermore, the increased levels of nitric oxide synthase within the lungs of the hypoxic swine were not accompanied by a proportional increase in enzyme activity. These findings suggest that the development of pulmonary hypertension in infants with congenital cyanotic disease is not due to decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
3
9
0
Order By: Relevance
“…The measurement 20 mm Hg is close to the normal seen after birth when the pressure falls from 25 to 16 mm Hg by 14 d (1) and 45 mm Hg is a similar pressure to that recorded in hypoxic conditions in young piglets (11). However, the pressures used had little effect on the size or responsiveness of the arteries, whether normal or hypertensive.…”
Section: Hypoxic Pulmonary Resistance Arteriessupporting
confidence: 80%
“…The measurement 20 mm Hg is close to the normal seen after birth when the pressure falls from 25 to 16 mm Hg by 14 d (1) and 45 mm Hg is a similar pressure to that recorded in hypoxic conditions in young piglets (11). However, the pressures used had little effect on the size or responsiveness of the arteries, whether normal or hypertensive.…”
Section: Hypoxic Pulmonary Resistance Arteriessupporting
confidence: 80%
“…The same perfusion pressure was used in all preparations, to standardise the procedure. The higher pressure of 45 mm Hg is similar to that found in piglets raised under hypoxic conditions [17]. Also, hypertensive newborn infants can have a transient or sustained increase in pulmonary arterial pressure to a similar level.…”
Section: Discussionsupporting
confidence: 75%
“…In our study, it was predictable that there was expression of eNOS in all groups. Whole lung eNOS mRNA was also increased in rats (Shaul et al, 1995) and piglets (Scarborough et al, 1998) with chronic hypoxic pulmonary hypertension. By contrast, McQuillan et al (1994) reported that eNOS expression decreases in pulmonary hypertension and Moreno de Sandino and Hernandez (2003) also demonstrated that hypoxia-induced pulmonary hypertension in broilers is associated with a decrease in endothelial-derived NO expression in pulmonary vessels.…”
Section: Discussionmentioning
confidence: 90%